Biochemical changes in blood under Cr6+. - Kuzenko, E. V.; Romaniuk, A. M.; Butko, H. Yu.; Logvinova, H. V. (Морфологія / Morphologia / Morfologìâ, 2013)
Background. For the manufacture of dentures many different alloys containing chromium are used. Interaction with oral fluid, organic acids and food, results in formation of Cr3+, Cr6+ ions, but their influence on the whole organism is poorly investigated. Objective. To analyze the biochemical changes in blood plasma during the influence of Cr6+ ions. Methods. 15 animals of experimental group were receiving drinking water with potassium dichromate in a dose of 0,2 mol/l. Rats of control group (5 individuals) drank usual drinking water. Animals were led out of experiment on the 20th, 40th and 60th days after the beginning of introduction of potassium dichromate. Results. It was established that at the beginning of experiment the blood biochemical indicators of control and the 1st experimental groups differed by its content. Increase of urea concentration led to suspicion about violation of a glomerular filtration, damage of a kidney parenchyma and tissue disintegration. On the 20th and 40th days of experiment the symptoms of acidosis and increase of potassium ions concentration in blood plasma were defined. Continuous and dynamic increase of creatin-phosphokinase was observed during 60 days of experiment. Conclusion. Biochemical changes in blood under the influence of Cr6+ ions evidence their toxic action on an organism. Especial concern is caused by changes of ionic composition and increase of the atherogenic index of blood plasma on the 40th day of experiment. Substantial increase of the creatin-phosphokinase level indicates general somatic influence of chromium ions.